2011
DOI: 10.1051/0004-6361/201117065
|View full text |Cite
|
Sign up to set email alerts
|

The ionization equilibrium and flare line spectra for the electron distribution with a power-law tail

Abstract: Context. Electron energy spectra exhibiting a high-energy tail are commonly observed during solar flares. Aims. We investigate the influence of the high-energy tail and thermal or nonthermal plasma bulk on the ionization equilibrium of Si and Si flare line spectra. Methods. We construct a realistically composed distribution that reflects the fits to RHESSI observations. We describe the high-energy tail by a power-law distribution and the bulk of the electron distribution by either the Maxwellian or n-distribut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 40 publications
0
16
0
Order By: Relevance
“…The RHESSI spectra indicated that the emission measure of the n-distribution is much higher than for the Maxwell one (Tables A.7, A.8); so the line spectrum of the n-distribution dominates over the Maxwell spectrum, which agrees with the observations (Dzifčáková et al 2011b). Finally, the electron densities of the power-law distribution, as well as of the electrons producing the type III bursts, are too low compared to the other two assumed distributions to have any significant effects on the studied RESIK Si line spectrum; see also the recent results on a combined distribution composed of the n-distribution and the power-law tail (Dzifčáková et al 2011a).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…The RHESSI spectra indicated that the emission measure of the n-distribution is much higher than for the Maxwell one (Tables A.7, A.8); so the line spectrum of the n-distribution dominates over the Maxwell spectrum, which agrees with the observations (Dzifčáková et al 2011b). Finally, the electron densities of the power-law distribution, as well as of the electrons producing the type III bursts, are too low compared to the other two assumed distributions to have any significant effects on the studied RESIK Si line spectrum; see also the recent results on a combined distribution composed of the n-distribution and the power-law tail (Dzifčáková et al 2011a).…”
Section: Discussionmentioning
confidence: 95%
“…Thus, the ratio Si xiii/Si xiid is extremely sensitive to the shape of the electron distribution function. For detailed information see Dzifčáková et al (2011a), who investigate the influence of the non-thermal plasma bulk and the high-energy tail on the Si ionization and its line spectra. The observed enhanced intensities of satellite lines ) require an increased number of particles at Si xiid energy in comparison to the Maxwell distribution (Figs.…”
Section: Diagnostics Of the N-distributionmentioning
confidence: 99%
“…Credit: Kulinová et al (2011), reproduced with permission c ESO. Dzifčáková, Homola, and Dudík (2011) calculated theoretical spectra for a composite np-distribution characterized by a n-distribution bulk and a powerlaw tail. They showed that such a composite distribution is also able to produce enhanced dielectronic satellites, while the Maxwellian distribution with powerlaw tails alone cannot produce this effect.…”
Section: Non-maxwellian Analysis Of X-ray Line Spectramentioning
confidence: 99%
“…Diagnostics for κ based on line intensity ratios have been proposed (Dzifčáková & Kulinová 2011;Dudík et al 2014Dudík et al , 2015. One limitation of the reverse-engineering method has been that it is a complicated process to obtain all of the atomic data necessary to calculate these ratios, and so only data for certain discrete values of κ are available.…”
Section: Level Populations and Line Emissivitiesmentioning
confidence: 99%